Activation of the Grinding Process by Using the Adsorption Effect When Grinding Materials (Eurasian Research Bulletin, 2022)
The article discusses methods for reducing energy consumption for grinding building materials, saving electricity, and activating the grinding process by reducing its strength when using adsorption action, which is a physical and chemical method during grinding